2009
DOI: 10.18632/aging.100008
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in gene expression and sensitivity to genotoxic stress following HdmX or Hdm2 knockdown in human tumor cells harboring wild-type p53

Abstract: While half of all human tumors possess p53 mutations, inactivation of wild-type p53 can also occur through a variety of mechanisms that do not involve p53 gene mutation or deletion. Our laboratory has been interested in tumor cells possessing wild-type p53 protein and elevated levels of HdmX and/or Hdm2, two critical negative regulators of p53 function. In this study we utilized RNAi to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 44 publications
5
21
0
Order By: Relevance
“…Microarray analysis of these cells revealed a subset of p53 target genes with anti-proliferative properties and a further subset of genes which are transactivated by E2F as cells transverse the G 1 -S boundary. 38 In conclusion, in this study we have shown that both the cell type N or S and MYCN are involved in the downstream response to irradiation induced DNA damage and that these effects are at least partially p53-dependent. Also, there were no MYCN coamplified genes that were found to be associated with failure to G 1 arrest.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 56%
“…Microarray analysis of these cells revealed a subset of p53 target genes with anti-proliferative properties and a further subset of genes which are transactivated by E2F as cells transverse the G 1 -S boundary. 38 In conclusion, in this study we have shown that both the cell type N or S and MYCN are involved in the downstream response to irradiation induced DNA damage and that these effects are at least partially p53-dependent. Also, there were no MYCN coamplified genes that were found to be associated with failure to G 1 arrest.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 56%
“…These recent advancements in the field assigned an essential role of the RING domain of MdmX in negative regulation of p53 in vivo, just like Mdm2 RING domain, through p53 degradation. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] because activation of p53 can lead to apoptosis, quiescence and senescence. [21][22][23][24][25][26][27][28][29][30][31] Furthermore, the ability of p53 to choose between quiescence and senescence is determined by its ability to inhibit mTOR.…”
Section: Introductionmentioning
confidence: 99%
“…In order to study novel p53 regulated genes, a microarray experiment was completed where the negative regulators of p53 (Hdm2 and HdmX) were silenced in MCF7 breast carcinoma cells using siRNA technology (Heminger et al, 2009). MCF7 cells contain wild-type p53; therefore, knocking down Hdm2 and HdmX allowed for the nongenotoxic stress induction of p53.…”
Section: Ypel3 and P53 Familymentioning
confidence: 99%
“…MCF7 cells contain wild-type p53; therefore, knocking down Hdm2 and HdmX allowed for the nongenotoxic stress induction of p53. This led to a G1 phase cell cycle arrest along with sensitization of the arrested MCF7 cells to DNA damage (Heminger et al, 2009). From analysis of the microarray data, a novel p53 target was discovered named YPEL3.…”
Section: Ypel3 and P53 Familymentioning
confidence: 99%